KOMUNIKASI INTERPERSONAL DALAM DAKWAH BERBASIS STIFIn: (Studi Komunikasi Tentang Kecerdasan Kepribadian Seorang Da’i dalam Komunikasi Interpersonal Dakwah) - Rahmah, Fatimatu (DECODING: Jurnal Mahasiswa KPI, 2020)
The author gives the title of this thesis "Interpersonal Communication inSTIFIn-Based Da'wah", communication is the process of delivering messages bycommunicators to communicants through media which have certain consequences.Whereas in a communication there are several types of communication, includinginterpersonal communication, the meaning is communication that is done tooneself, which is done intentionally or unintentionally. Interpersonal communication is often used in the da'wah process, because byusing interpersonal communication, the message of da'wah can be conveyedeffectively. In preaching, it should pay attention to the conditions of thecommunicants so that the message of da'wah can be received well, so that theauthors analyze how interpersonal communication in STIFIn-based da'wah.Because in the STIFIn concept, the communicant can see how the state of mind ofa communicant is so that the communicator can choose material that is balancedwith the way of thinking of each recipient of the message. To fulfill the theoretical basis of the appropriate literature review, the authordescribes the definitions, patterns and methods of interpersonal communication inSTIFIn-based da'wah. The author conducts library research or what is called library research because itis not possible to conduct direct or field research. In this writing, the writer uses the method of writing literature or searchingfor sources and data by looking at documents, or books related to interpersonal communication, preaching and STIFIn concepts as well as articles related to whatthe author is researching. Based on the research that the author has done, that interpersonalcommunication in STIFIn-based da'wah is a method of how a communicatorconveys his message to a communicant with the interpersonal communicationmethod and sees the quality of the way of thinking of a communicant to receive hisda'wah message with the STIFIn concept which is done by scanning the tip fingersto see the personality of each individual, so that the message can be received welland the process of da'wah can be carried out effectively.